2022
DOI: 10.1111/nyas.14905
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin is essential for bone homeostasis and immunology

Abstract: Intercellular communication or crosstalk between immune and skeletal cells is considered a crucial element in bone homeostasis modulation. Progranulin (PGRN) is an autocrine growth factor that is structured as beads‐on‐a‐string and participates in multiple pathophysiological processes, including atherosclerosis, arthritis, neurodegenerative pathologies, cancer, and wound repair. PGRN functions as a competitor that binds to tumor necrosis factor receptor 1 (TNFR1), thereby blocking the TNF‐α pathway. PGRN is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
(296 reference statements)
0
3
0
Order By: Relevance
“…Atsttrin and PGRN have similar physiological functions and can also bind to TNFR and inhibit TNF-α signaling pathways 20 , 21 . Moreover, Atsttrin showed longer half-lives and stronger therapeutic effects in previous studies compared to PGRN 21 23 . At the same time, we found that Atsttrin plays an important role in protecting early inflammatory arthritis in animal models and promoting cartilage repair 20 , 21 .…”
Section: Introductionmentioning
confidence: 81%
“…Atsttrin and PGRN have similar physiological functions and can also bind to TNFR and inhibit TNF-α signaling pathways 20 , 21 . Moreover, Atsttrin showed longer half-lives and stronger therapeutic effects in previous studies compared to PGRN 21 23 . At the same time, we found that Atsttrin plays an important role in protecting early inflammatory arthritis in animal models and promoting cartilage repair 20 , 21 .…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, in the PGRN‐knockout mice, PGRN was essential for maintaining bone mass by inhibiting TNF‐α‐induced osteoclastogenesis and promoting osteoblastogenesis (Noguchi et al, 2015). A recent review has also comprehensively summarized the active role of PGRN in bone homeostasis (Chen et al, 2022). In brief, our findings are consistent with those of the above studies, indicating that PGRN could also promote periodontal regeneration under non‐surgical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PGRN can exert its immunomodulatory effects by inhibiting M1 macrophage polarization and Th17 cell differentiation and by promoting M2 macrophage polarization and Treg cell differentiation (Chen, Wang, et al, 2020; Wang et al, 2022). PGRN also plays a crucial role in maintaining bone homeostasis, particularly in the context of inflammation (Chen et al, 2022). Our research group has evaluated the function and application potential of PGRN in periodontitis in many aspects (Chen et al, 2019; Chen, Yu, et al, 2020; Li et al, 2018; Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%